ANALISIS STRUKTUR DAN KAIDAH KEBAHASAAN TEKS CERITA ULANG BIOGRAFI KARYA MAHASISWA PROGRAM STUDI BIMBINGAN KONSELING IKIP PGRI BALI - Sudarti, Ni Wayan (Widyadari: Jurnal Pendidikan, 2019)
The structure and language rules of the biography text story revised by the Guidance Counseling study program students are revealed in this study. Specific objectives in this study, namely to determine the structure of the biography retelling text content and to find out the language rules of biography retelling texts. This study uses several theories, among others: 1) understanding text, 2) re-understanding of the story, 3) the structure of the retelling text, and 4) the language principle of the retelling text, The method in this study are: 1) the method of determining the research subject, 2) research subject approach methods, 3) data collection methods, and 4) data processing methods. Judging from the structure of the content and linguistic rules, the results of research on biography text stories written by Counseling Guidance study program students, the average result was 82.01. Conversion score of 82.01 is in the range 81-85, with the predicate B (good). Then the results can be categorized as good.